2012
DOI: 10.33073/pjm-2012-016
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Candida albicans Pleomorphic Forms: Phase-Contrast Microscopy, Scanning and Transmission Electron Microscopy

Abstract: A modified method of glutaraldeyde-osmium tetroxide fixation was adjusted to characterize the ultrastructure of Candida albicans pleomorphic forms, using phase-contrast microscopy, scanning electron microscopy and transmission electron microscopy. The discovered morphological criteria defining the individual morphotypes are discussed in terms of mycological and histopathological diagnostics of candidiasis. The relations are discussed between fungal pleomorphism, virulence and susceptibility of different morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Although the distinguishing criteria between various morphotypes are still a matter of debate, some of them have been established based upon transmission electron microscopy (TEM) by Müller and Melchinger (2006) . Our previous studies ( Staniszewska 2009 ; Staniszewska et al , 2011 , 2012 ) based upon phase-contrast microscope as well as transmission and scanning electron microscopes partially provided criteria of C. albicans wild type morphotypes i.e. : criteria of breakable septa typical for blastoconidia and pseudohyphae, features of massive septa characterizing true hyphae, privileged areas of budding or branching, relations between the cultivation conditions and growth of particular pleomorphic forms, fibrous appearance at the outer surface of the cell wall of different morphotypes, cellular and hyphal organization of mycelium-like aggregates.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although the distinguishing criteria between various morphotypes are still a matter of debate, some of them have been established based upon transmission electron microscopy (TEM) by Müller and Melchinger (2006) . Our previous studies ( Staniszewska 2009 ; Staniszewska et al , 2011 , 2012 ) based upon phase-contrast microscope as well as transmission and scanning electron microscopes partially provided criteria of C. albicans wild type morphotypes i.e. : criteria of breakable septa typical for blastoconidia and pseudohyphae, features of massive septa characterizing true hyphae, privileged areas of budding or branching, relations between the cultivation conditions and growth of particular pleomorphic forms, fibrous appearance at the outer surface of the cell wall of different morphotypes, cellular and hyphal organization of mycelium-like aggregates.…”
Section: Introductionmentioning
confidence: 93%
“…: criteria of breakable septa typical for blastoconidia and pseudohyphae, features of massive septa characterizing true hyphae, privileged areas of budding or branching, relations between the cultivation conditions and growth of particular pleomorphic forms, fibrous appearance at the outer surface of the cell wall of different morphotypes, cellular and hyphal organization of mycelium-like aggregates. Under in vitro conditions, the interconversion among the cell types are induced by modifying the pH, temperature, and/or serum concentration in the growth medium ( Barnett 2008 ; Kruppa 2009 ; Staniszewska 2009 ; Noble et al , 2010 ; Staniszewska et al , 2011 , 2012 ). Moreover, the success of C. albicans as a pathogen is related in part to polymorphism as strains blocked in morphogenesis proved to be non-virulent ( Lo et al , 1997 ; Kumamoto and Vinces, 2005 ; Yang et al , 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different from the control cells, morphological observation showed a predominance of single, isolated blastoconidia over the budding cells and no true hyphal development. These results suggest that the BTME substantially affected the morphogenetic transition of C. albicans, which is crucial to its virulence (Staniszewska et al 2012). The ability to produce hyphae (and them switch between yeast and filamentous forms) is of extreme importance to the pathogenesis of candidiasis and is considered the central virulence attribute (Berman & Sudbery 2002;Dalle et al 2010;Mayer et al 2013).…”
Section: Discussionmentioning
confidence: 89%
“…Depending on environmental conditions, C. albicans can assume three different morphotypes during its development: blastoconidial, pseudohyphal and hyphal forms. Furthermore, C. albicans easily develops into a biofilm on surfaces, which when compared to planktonic cells, displays stronger resistance to a wide variety of antifungal agents (Staniszewska et al 2012;Ma et al 2015). Different from the control cells, morphological observation showed a predominance of single, isolated blastoconidia over the budding cells and no true hyphal development.…”
Section: Discussionmentioning
confidence: 97%
“…In the mycological field, several studies have demonstrated that SEM is a good method for observing fungal ultrastructure in nails with onychomycosis [ 5 – 9 ]. Observation of a dermatophyte by SEM [ 5 – 9 ] reveals hyphae with clearly visible branches and septa or arthroconidia, whereas analysis of Candida in culture medium by SEM [ 10 , 11 ] often shows pseudohyphae, blastospores, budding, and a ring of bud scars. Thus, SEM is a good tool for observing fungal morphology.…”
Section: Introductionmentioning
confidence: 99%